Political Activism as a Determinant of Clientelistic Transfers: Evidence from an Indian Public Works Program - Nancy Chau; Yanyan Liu; Vidhya Soundararajan (Institute of Labor Economics (IZA), 2018)
Are political activists preferentially targeted by politicians engaging in clientelistic transfers to bolster political support? We provide the first model to highlight two possible rationales for such transfers: to mobilize support from the activists themselves, or to mobilize support from electors these activists have influence over. Using novel household data on ex ante political affiliation and jobs received subsequent to large-scale decentralized workfare program in India, we find that activists are indeed preferentially targeted, and furthermore, such transfers are more pronounced in locations where citizen political involvement is less common, and in remote and less connected areas where activists' role in information transfers is most critical. We argue that the evidence is consistent with the use of transfers to leverage the influence of activists over the decision-making of other electors. Our results are not driven by self selection, reverse causality, and other program transfers, and are robust to alternate definitions of "activism".
Keywords: D7; H5; 330; political clientelism; political activism; NREGS; India